Perlindungan Konsumen Atas Praktik Pemindahan Isi Gas LPG Tidak Sesuai Standar Operasional Perusahaan - Rahmawati, Alfina Kusuma; Kusuma, Ajeng Pramesthy Hardiani; Yasa, I Wayan (Acten Journal Law Review, 2025)
LPG gas is a primary necessity for the community because it is more practical and efficient than firewood or kerosene. High demand has triggered illegal practices by some businesses, namely transferring subsidized gas cylinders to non-subsidized cylinders using tools that do not meet standards. This action risks causing explosions and losses for consumers. This study aims to analyze the forms of legal protection for consumers, the legal implications for business actors, and efforts to resolve disputes resulting from the distribution of LPG gas that does not comply with company operational standards. The research method used is normative juridical with a statute approach and a conceptual approach. The results of the study show that Legal protection for consumers against the distribution of LPG that is non-compliant with standard operating procedures is implemented through both internal and external mechanisms. Internally, protection is realized through agreements between consumers and business actors to safeguard consumer rights; conversely, external protection is provided by the State through the Consumer Protection Law, which guarantees security, safety, comfort, and legal certainty. This protective framework is further reinforced by the role of the National Consumer Protection Agency (BPKN), which is empowered to supervise and take enforcement action against business actors in violation of the law.. Business actors can be subject to criminal, administrative, and civil sanctions in accordance with Consumer Protection Law, the Oil and Gas Law, and the ESDM Ministerial Regulation. Meanwhile, consumer dispute resolution can be pursued through litigation in court or non-litigation through the BPSK. Consistent law enforcement and strict distribution supervision are necessary to provide legal certainty, safety, and optimal protection for LPG consumers in Indonesia.